Religious Marriage in Indonesia in the Perspective of Islamic Law and Positive Law in Indonesia : Legal Comlexities and the Issuance of Supreme Court Circular Letter No. 2 of 2023: Perkawinan Beda Agama Di Indonesia Dalam Perspektif Hukum Islam Dan Hukum Positif Di Indonesia Kompleksitas dan Implikasi Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 - Rusman, Rusman; Hidayat , Yusuf; Rifai, Anis (Universitas Muhammadiyah Sidoarjo, 2023)
This normative legal research aims to clarify the regulation of interfaith marriages in Indonesia, considering both positive law and Islamic law perspectives, and assess the impact of Circular Letter No. 2 of 2023 on legal certainty in this matter. The study found that the 1974 Marriage Law lacks comprehensive protection for interfaith marriages. Islamic law, particularly according to the Indonesian Ulema Council (Mui), tends to prohibit such marriages due to perceived violations of fiqh principles, such as preventing harm (sadd al-zarî’ah). Despite these differing opinions, Circular Letter No. 2 of 2023 is expected to provide legal clarity and potentially resolve the controversy surrounding interfaith marriages in Indonesia. The Supreme Court's prohibition on interfaith marriages has sparked debates and protests in society, with some activists arguing that the court's order is a clear violation of people's constitutional rights, such as freedom of religion. Highlights: The study aims to clarify the regulation of interfaith marriages in Indonesia, considering both positive law and Islamic law perspectives, and assess the impact of Circular Letter No. 2 of 2023 on legal certainty in this matter. The 1974 Marriage Law lacks comprehensive protection for interfaith marriages, and Islamic law tends to prohibit such marriages due to perceived violations of fiqh principles. Despite differing opinions, Circular Letter No. 2 of 2023 is expected to provide legal clarity and potentially resolve the controversy surrounding interfaith marriages in Indonesia. Keywords: Interfaith Marriages, Legal Certainty, Islamic Law, Indonesian Ulema Council, Circular Letter No. 2 of 2023.